Pengaruh Variasi Suhu Kondensor terhadap Kinerja Rotary Vacuum Evaporator pada Ekstraksi Meniran (Phyllanthus Niruri) - Dwi Heru Siswantoro; Yayang Permadi; Revvan Rifada Pradiza; Sekar Sari; Rizka Yusvida (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study analyzes the effect of condenser temperature variation on the performance of a rotary vacuum evaporator (RVE) in extracting Phyllanthus niruri solution. Three condenser conditions, 23 °C, 30 °C, and without cooling, were tested, each with five replications. Observed parameters included evaporation time, mass reduction rate, energy consumption, and flavonoid content, which were analyzed statistically using Analysis of Variance (ANOVA). Results showed that the 23 °C condenser achieved the highest mass reduction rate (3.78 g/min) and the lowest energy consumption (0.14 kWh). At 30 °C and without cooling, mass reduction rates decreased to 3.02 g/min and 2.24 g/min, while energy consumption rose to 0.19 kWh and 0.20 kWh. The 23 °C condenser also produced the highest flavonoid content (11.9 mg/mL), confirming optimal thermal efficiency. This work fills the research gap on the effect of condenser temperature on energy efficiency and extract quality in RVE systems and provides a basis for developing energy-efficient evaporators for small-scale herbal industries.